Relationship between selection of dosage forms of vitamin D receptor activators and short-term survival of patients on hemodialysis - Eri Koshi-Ito (Taylor & Francis Group, 2021)
Background The benefits of vitamin D receptor activators (VDRAs) for patients with chronic kidney disease are well recognized. However, the optimal criteria for patient selection, dosage forms, and duration providing the highest benefit and the least potential risk remain to be confirmed. Materials and methods The study population was derived from the Aichi Cohort Study of Prognosis in Patients Newly Initiated into Dialysis, a multicenter prospective cohort study of 1520 incident dialysis patients. According to the VDRA usage status in March 2015 (interim report), the 967 patients surviving after March 2015 were classified into three groups: without VDRA (NV, n = 177), oral VDRA (OV, n = 447), and intravenous VDRA (IV, n = 343). Mortality rates were compared using the log-rank test, and factors contributing to all-cause mortality were examined using both univariate and multivariate Cox proportional hazard regression analyses. Results There were 104 deaths (NV, n = 27; OV, n = 53; IV, n = 24) during the follow-up period (1360 days, median), and significant differences in cumulative survival rates were observed between the three groups (p = 0.010). Moreover, lower all-cause mortality was associated with IV versus NV (hazard ratio, 0.46 [95% confidence interval 0.24–0.89]; p = 0.020). Conclusion This study demonstrated the impact of the VDRA dosage form on the short-term survival of incident hemodialysis patients during the introduction period. Our results suggest that relatively early initiation of intravenous VDRA in patients beginning hemodialysis may have some clinical potential.